Cover Picture: Electrospinning Hetero‐Nanofibers of Fe3C‐Mo2C/Nitrogen‐Doped‐Carbon as Efficient Electrocatalysts for Hydrogen Evolution (ChemSusChem 12/2017). Issue 12 (12th June 2017) - Lin, Huanlei; Zhang, Wenbiao; Shi, Zhangping; Che, Minwei; Yu, Xiang; Tang, Yi; Gao, Qingsheng
Abstract : The Cover picture shows a hurdle race with different hurdles corresponding to the varied energy barriers of the hydrogen evolution reaction. In this work, electrospinning followed by pyrolysis is introduced to construct Fe3 C‐Mo2 C/N‐doped carbon hetero‐nanofibers and accomplish the synergistically enhanced elementary steps, as illustrated by the low hurdles in the runway. Such synergy results in the benchmarking performance of noble‐metal‐free electrocatalysts. This study opens up new opportunities to explore high‐performance catalysts through interfacial engineering. More details can be found in the Full Paper by Lin et al. onpage 2597 in Issue 12, 2017 (DOI:10.1002/cssc.201700207 ).